1616b Questionnaire based evaluation of the whole-life history of solar uv radiation exposure in a group of patients in italy. (24th April 2018) - Modenese, Alberto
Abstract : Introduction: An adequate evaluation of the ultraviolet (UV) cumulative exposure is a major problem in epidemiological studies on chronic skin damage. Questionnaires may be applied as useful tools. For these reasons, a detailed questionnaire for the evaluation of individual cumulative exposure to Solar Radiation (SR) of outdoor workers (OWs) was developed, to investigate the associations between exposure and the presence of skin damage. Method: Based on ICNIRP publications, a detailed questionnaire, considering both working and leisure UV exposure, was developed and applied in group of volunteers and in patients affected by Non Melanoma Skin Cancers (NMSCs), to evaluate whole-life SR exposure and the relevant factors associated, including exposure habits, environmental factors and use of protections. Results: In patients with NMSCs, we found that the co-presence of in situ squamous cell carcinoma (SCC) and invasive NMSCs was more frequent in OWs than in indoor workers (IWs), as was also the frequency of multiple skin lesions. The prevalence of lesions in the most exposed body areas, as the face, was significantly higher in OWs, while working in shades was negatively associated with skin lesions. Also working posture was relevant: adopting a bent-over position was associated with lesions on the head. For leisure activities, the questionnaire application confirms the relevant role of tanning beds, in particular for body areas usually not highly exposed to SR, and the relevance of intense exposure in the middle hours of the vacation days ('sunbaths'), significantly associated with NMSCs presence. Conclusion: A detailed questionnaire-based evaluation in subjects with NMSCs can be very useful for estimating the whole-life individual UV exposure and the relevancy of occupation. Furthermore, an integration with personal dosimetric UV measurements can lead to a semi-quantitative evaluation, to set out exposure levels and different exposure modalities (e.g. intermittent vs cumulative) for various occupations and, possibly, for the different SCs.